PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER PADA MATERI SALING KETERGANTUNGAN DALAM EKOSISTEM DI KELAS VII MTs NEGERI TANAH JAWA T.P 2014/2015 - Winda Afriza, Afni; Rosenta Purba, Ika (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2022)
This study aims to determine differences in student learning outcomes using the Numbered Heads Together learning model. This research is an experimental study with a pre-test, post-test design. The population was 203 students, and the sample size was 80 students (Cluster Random Sampling). Class VII-2 served as the experimental class, and class VII-4 as the control class. Data analysis was conducted by calculating the average score and standard deviation, and hypotheses were tested using the t-statistic or t-test at a significance level of α = 0.05. The average pre-test score for the experimental class was 44.25, and the average post-test score for the experimental class was 78.37. The average pre-test score for the control class was 38.50, and the average post-test score for the control class was 65.25. This indicates an improvement in the topic of interdependence in ecosystems in class VII of MTs Negeri Tanah Jawa in the 2014/2015 academic year, with a score of 34.12. The results of the hypothesis test using the t-test obtained a calculated t (7.68) > t table (2.00), therefore H0 is rejected and Ha is accepted, meaning there is a difference in student learning outcomes using the Numbered Heads Together learning model on interdependence in ecosystems in grade VII MTs Negeri Tanah Jawa in the 2014/2015 academic year. It was concluded that there is a significant difference in learning outcomes using the Numbered Heads Together learning model on interdependence in ecosystems in grade VII MTs Negeri Tanah Jawa in the 2014/2015 academic year.